2011
DOI: 10.1597/10-133
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Studies in the Nigerian Population Implicate an MSX1 Mutation in Complex Oral Facial Clefting Disorders

Abstract: Background Orofacial clefts are the most common malformations of the head and neck with a World-wide prevalence of 1/700 births. They are commonly divided into CL(P) and CP based on anatomical, genetic and embryological findings. A Nigerian craniofacial anomalies study “NigeriaCRAN” was set up in 2006 to investigate the role of gene-environment interaction in the etiology of orofacial clefts in Nigeria. Subjects and Methods DNA isolated from saliva from the Nigerian probands was used for genotype association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
2
7

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 43 publications
(68 reference statements)
1
36
2
7
Order By: Relevance
“…Screening of the MSX1 gene revealed a missense variant (Ala40Gly), which was associated with orofacial clefting with tooth agenesis in a US population . More recently, another study in a Nigerian population demonstrated the association of this variant with isolated orofacial clefting . We found this variant in only eight patients (Tables S1 and ).…”
Section: Discussionmentioning
confidence: 57%
“…Screening of the MSX1 gene revealed a missense variant (Ala40Gly), which was associated with orofacial clefting with tooth agenesis in a US population . More recently, another study in a Nigerian population demonstrated the association of this variant with isolated orofacial clefting . We found this variant in only eight patients (Tables S1 and ).…”
Section: Discussionmentioning
confidence: 57%
“…In particular, few studies have been done in African-derived populations; given their low birth prevalence, results from such populations could provide particular insights into OFC. Two studies have tested the loci significant in Caucasians and Asians, with no significant findings to date (21, 148). Other questions come from OFC epidemiology features, such as, is there a difference in risk variants for multiplex versus sporadic cases?…”
Section: Future Directions and Challengesmentioning
confidence: 99%
“…The association of the FOXE1 gene with NSCL/P has been confirmed in Thai, Caucasian and Han Chinese populations . However, some studies have shown that there is no significant correlation between FOXE1 and NSCL/P …”
Section: Discussionmentioning
confidence: 95%